EFFECT OF CLIMATE CHANGE ON WILDLIFE SPECIES IN DAJIN BATURIYA WETLAND AREA OF HADEJIA LOCAL GOVERNMENT AREA OF JIGAWA STATE - Abdullahi, Tijjani Yahaya; Karage, Abdulrasheed Muhammad; Ismail, Faiz Tijjani; Ahmad, Musa Musawa; Babanta, Shuaib Uba (FUDMA Journal of Sciences, 2026)
The study focused on effects of climate change on wildlife species in Baturiya wetland Area in Jigawa state. The methodology employed in the study was sampled plots. The results reveal that decreasing cold fronts, decrease in precipitation, decreasing vegetation structure, soil moisture and increasing heat intensity are the effects of climate change and on other hand the causes of climate change on wildlife specie in Dajin baturiya wetland  include overgrazing, logging, wildfires, illegal mining and erosion. It also identifies ant poaching, fire tracing, erosion control and tree planting as measures to mitigate the impacts of climate change in the study area.The findings show that in all the four plot there exist factors causing climate change. These causes identified include overgrazing Which expose the bare soil to sunlight and erosion. Illegal logging, wildfires which kills fauna and flora in the area. Erosion exposes the roots and uproot trees. The recommendations are the concern authorities should beef up ant poaching patrol so as to stop humans from entering the area and setting fires, cutting trees, grazing and killing animals. Environmental education campaigns, should be carried out in the communities around the area on conservation and the impacts of climate change and global warmingImproving legal and political frameworks for climate change, global warming and the environment in general. The work would help the policy makers, stakeholders to achieve  goals especially in the area selected, Baturiya wetland of Kirikasamma local government in Jigawa State.
Keywords: Wildlife species; Climate Change; Wetland; Descriptive Statistics; Plots